Assessment on Level of Knowledge Regarding Child Sexual Abuse among School Children at Kattankulathur High School (Medico Legal Update, 2021)
Child sexual abuse (CSA) is a serious and widespread problem in India as it is in many parts of the worldtoday. Objective: The aim of this study was assess the knowledge on child sexual abuse among schoolchildren at Kattankulathur High School and to associate the knowledge on child sexual abuse among schoolchildren at kattankulathur High School with their demographic variables.Method : Quantitative approach and non-experimental descriptive research design was used. The datacollection included two parts. Part A: Demographic variables, Part B: A Structured questionnaire to assessknowledgeon child sexual abuse among school children. 180 school childrenwho fulfilled the inclusioncriteria were selected as samples using non probability convenient sampling technique. The study wasconducted at kattankulathur High School, Kancheepuram dt..Results: The data were analyzed and interpreted based on the objectives using descriptive and inferentialstatistics.Among 180 school children 90.6% of them had Moderately adequate Knowledge, 9.4% of themhad Inadequate knowledge and None of them had adequate knowledge. The p-values are not significant sincethey are not less than 0.05 hence we can say that there is no significant association between the demographicvariables and the knowledge on Child Sexual Abuse at 5% level. Conclusion: child sexual abuse is animportant contributor topsychological and emotional disorders, that some children and adolescents maynever overcome.